Kepiting Bakau (Scylla sp.) Teluk Bintuni Papua Barat : Strategi Pengelolaan dan Perijinan usaha - Ahmad Fahrizal; Kusuma Dewi; ABu Darda Razak; Irwanto Irwanto (Jurnal Airaha, 2021)
The purpose of this study was to determine the licensing method of fishing for mud crab (Scylla sp.) and to determine the stages of the strategy undertaken to support the management of traditional fishery resource potential in Manimeri District. This research was started from 18 August to 8 Oct 2019, located in Manimeri District, Banjar Ausoy Village and Korano Jaya, Teluk Bintuni Regency, West Papua Province. The data collection techniques and methods used in the study were observation, interviews with informants using questionnaires and Focus Group Discussions (FGD) in Basic Training on Traditional Community-Based Fisheries Management in Manimeri District. The analysis used is the SWOT analysis. The results showed that fishing efforts carried out by migrant fishermen in the areas of Kampung Banjar Ausoy and Korano Jaya in catching crabs must have a fishing license through the knowledge of the owner of the customary rights, namely from the Wamesa Tribe. Management strategies for traditional fisheries resource potential in Manimeri District, namely: 1) Optimizing fishery resource management in Manimeri District, 2) Strengthening law and institutional management of fishery resources, 3) Improving the quality of the marketing system, and 4) Preserving the potential of capture fisheries resources.